PENGARUH IKLAN, HARGA, DAN KEPERCAYAAN MEREK TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK REVLON (Studi pada Mahasiswa S1 Universitas Diponegoro) - Puspita, Rahmilla Chairani; Suryoko, Sri (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2017)
In order to maintain the continuity, develop the company, and maintain its existence, the company is required to continue to provide competitive advantages by paying attention and managing the supporting aspects in marketing its products. High level of purchasing decision become the key to a company's success in selling their products. Revlon always place at top 5 of the survey published by Top Brand Index in 2014-2016 term, however Revlon has a vulnerable position displaced by its competitors. This can be seen from the decline of 4.7% in the foundation category from the first position in 2015 to second position in 2016 shifted by Wardah which significantly increased by 17.7% in 2016. This study aims to determine the influence of advertising, price, and brand trust on Revlon cosmetics purchase decision of the undergraduate students of Diponegoro University. Type of research is explanatory research with the population undergraduate students of Diponegoro University, and the number of sample taken is 100. The data collection techniques are questionnaire, documents, and literature review. The sampling technique is purposive sampling. The data analysis techniques are correlation test data analysis, determination test, simple linear regression test, multiple linear regression test, t test, and F test using IBM SPSS (Statistical Product and Service Solutions) program version 16.0 Based on the results of the analysis, it is concluded there is a positive and significant influence between advertising, price, and brand trust on purchase decision partially and simultaneously (together). There are other factors that influence the Purchase Decision. Therefore it can be advised that Revlon has to evaluate their message in Revlon advertisement, increase the discount frequency on certain events, and add some product variants.